The last girl - Kamna Kakkar (Research and Humanities in Medical Education, 2020)
This poem sums up my life as a doctor of anaesthesiology during the time of the Coronavirus pandemic. Anaesthesiologists stand at the forefront of this crisis because the sickest of the sick patients who test positive for Corona eventually require intubation and mechanical ventilation in the Intensive Care Unit. Some of them do not survive, making our job challenging not just medically, but even emotionally - heart-wrenchingly so.